Peran Advokasi Hukum Keluarga Islam dalam Membangun Keharmonisan Keluarga - Husna, Hafizhatul; Hanim, Azkia; Hadianto, Bagues; Rendy, Muhammad; Syamsiah, Syamsiah (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2025)
The family is a basic institution in society that plays an important role in shaping generations and maintaining social stability. In Islam, the family is not only a biological relationship, but also a vehicle for fostering morals, faith, and spiritual well-being. However, the challenges of modern life such as divorce, role conflict, and domestic violence threaten the harmony of Muslim families. This study aims to examine the role of Islamic family law advocacy in building family harmony amidst these dynamics. In the context of Islam, family advocacy is not just legal defense in court, but includes comprehensive efforts such as education, religious counseling, mediation, and family counseling. This study uses a descriptive qualitative approach based on a literature study of scientific literature, laws and regulations, and institutional practice documents. The results of the study indicate that sharia mediation and advocacy based on Islamic values ​​are highly effective in preventing divorce, improving communication between couples, and maintaining the mental stability of children as the most vulnerable party in household conflicts. Institutions such as BP4 and religious counselors play a key role in family law advocacy, especially in promoting the values ​​of sakinah, mawaddah, and rahmah. However, there are still challenges in implementing advocacy, such as low family law literacy, stigma against counseling, and limited resources. This study concludes that Islamic family law advocacy is an important instrument in maintaining the integrity of the household and creating a harmonious and resilient Muslim society.